IMPLEMENTASI MODEL QUEST BASED LEARNING BERBASIS VIRTUAL REALITY UNTUK MENINGKATKAN DEEP LEARNING DAN PROFIL PELAJAR PANCASILA DALAM PEMBELAJARAN IPAS KELAS VI SD. - Riri Komalasari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The development of this model aims to address the suboptimal science and social studies (IPAS) learning within the social interaction learning model at SDN Rawa Badak Utara 23 through Quest- Based Learning (QBL) integrated with Virtual Reality to create deep learning experiences and strengthen the Pancasila Student Profile. The implementation of the social interaction learning model was carried out over three meetings using a deep learning cycle. Activities included 360° virtual explorations to four countries, analytical discussions, mini- debates, and the creation of a